1999
DOI: 10.1128/aac.43.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Clarithromycin on a Transplanted Tumor in Rats

Abstract: The therapeutic antitumor effect of clarithromycin (CAM) was examined with the 13762NF mammary adenocarcinoma and F-344 rat system. When CAM treatment at a dosage of 2 mg/kg of body weight orally for 21 days was commenced after inoculation of the tumor, no significant decrease in death rate was observed, although the loss in body weight was less than that in the untreated group. When tumor-bearing (TB) rats were treated with CAM in combination with carboplatin or cyclophosphamide, a significant decrease in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Thus, it has been demonstrated that only spleen cells obtained from rats that have been immunized by allogeneic tumor cells followed by clarithromycin treatment showed a detectable cytotoxicity to the tumor cells. 30 These data and the fact that macrolide prescription in DPB patients is not accompanied by an increase in P. aeruginosa colonization 14 do not support an inference that long-term administration of these drugs results in imunosuppression.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, it has been demonstrated that only spleen cells obtained from rats that have been immunized by allogeneic tumor cells followed by clarithromycin treatment showed a detectable cytotoxicity to the tumor cells. 30 These data and the fact that macrolide prescription in DPB patients is not accompanied by an increase in P. aeruginosa colonization 14 do not support an inference that long-term administration of these drugs results in imunosuppression.…”
Section: Discussionmentioning
confidence: 92%
“…Limited trials have been conducted in cystic fibrosis, but preliminary results with azithromycin argue for more clinical investigations (160). Other clinical developments of macrolides outside their antibacterial effects concern their potential benefit in cancer, an effect demonstrated in animal models (336) and patients with lung cancer (254). The mechanisms underlying the antitumoral and anti-inflammatory activity of macrolides are no doubt multiple: studies done ex vivo and in animal models have demonstrated a modulation of neutrophil functions and proinflammatory cytokine production (200).…”
Section: Immunodepression and Anti-inflammatory Activity Of Antibactementioning
confidence: 99%
“…In ex vivo models, they also block invasiveness of cancer cells, including lung cancer cells [129,130]. Macrolides attenuate the release of TGF-b, the prototypical profibrotic cytokine and inducer of epithelial mesenchymal transition [131]. Macrolides also appear capable of suppressing both the release of and actions of matrix metalloproteinase [111,132].…”
Section: Anti-remodelling Actions?mentioning
confidence: 98%